HPLC fingerprinting/GC-MS analysis, and efficacy of Hypericum perforatum against cisplatin-induced hepato-renal toxicity in mice with insights into the TXNIP/NLRP3 pathway - Maha Badr Salem, Eman Adallah Morsi, Eman Ahmed El-Wakil, Naglaa Mohamed El-Lakkany, Tarek Abou-shousha, Heba Abdel-Hady (Journal of Applied Pharmaceutical Science, 2023)
Hypericum perforatum (HP) has antioxidant and anti-inflammatory characteristics. Nevertheless, its anti-inflammatory effects against hepato-renal injury have not been investigated. Therefore, this survey is designed to evaluate the prophylactic effect of HP extract against cisplatin- (CDDP-) induced hepato-renal toxicity in mice. Also, the active ingredients of HP were recognized. Hepato-renal toxicity was prompted by a single dose of CDDP (13 mg/kg, intraperitoneally). HP was tested at 50, 100, and 200 mg/kg/day for 10 days. Liver and kidney enzymes, oxidative stress, and inflammatory markers were examined, and histopathological examinations were performed. Total phenolic and flavonoid contents, besides 2,2-diphenyl-l-picrylhydrazyl radical scavenging activity, were assessed by identifying HP chemical compounds through high-performance liquid chromatography (HPLC) fingerprinting and gas chromatography-mass spectrometry. HP at 200 mg/kg improved hepatic and renal biochemical markers, reduced oxidative stress, and restored normal liver and kidney histology. Moreover, HP reduced inflammation by inhibiting TXNIP and NLRP3 tissue contents and cleaved caspase-1, interleukin-1β, and nuclear factor kappa-β expressions. The HPLC fingerprinting revealed high concentrations of ellagic acids, cinnamic acids, quercetin, and hesperidin, which may be responsible for alleviating hepato-renal damage. HP is an effective therapeutic agent against CDDP-induced hepato-renal toxicity and could be a realistic adjuvant therapy with CDDP for cancer treatment.
Keywords: Hypericum perforatum, cisplatin, inflammasome pathway, oxidative stress, phenolic compounds